Sovereignty, Identity, and Indigenous‐State Relations at the Beginning of the Twentieth Century: A Case of Exclusion by Inclusion1. Issue 3 (20th August 2015) - Pearcey, Mark
Abstract : The concept of civilization has played a central role in the work of the English School. Yet, most English School scholars concern themselves with the role of civilization in defining the relations between the members of international society. The Standard of Civilization stands as a case in point, for most English School scholars have examined this legal principle with reference to its role in defining membership in the society of states. This paper sets out to help us understand the role of the Standard of Civilization in defining relations between state and nonstate societies at the beginning of the twentieth century. It analyzes the Standard of Civilization and its role in defining Indigenous‐state relations and presents a case study analysis of Chief Levi General's diplomatic mission to the League of Nations on behalf of the Six Nations. The paper concludes with a discussion of the implications of its analysis for the theory and practice of IR, as well as the English School and its analytics.